2011
DOI: 10.1051/0004-6361/201117753
|View full text |Cite
|
Sign up to set email alerts
|

The rotational spectrum of protonated sulfur dioxide, HOSO+

Abstract: Aims. We report on the millimeter-wave rotational spectrum of protonated sulfur dioxide, HOSO + . Methods. Ten rotational transitions between 186 and 347 GHz have been measured to high accuracy in a negative glow discharge.Results. The present measurements improve the accuracy of the previously reported centimeter-wave spectrum by two orders of magnitude, allowing a frequency calculation of the principal transitions to about 4 km s −1 in equivalent radial velocity near 650 GHz, or one linewidth in hot cores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This level of agreement is similar to that obtained with the same level of theory (CcCR QFF) recently reported for HOCO + (Bizzocchi et al 2017). For example, the experimental D J fourth-order distortion constant differs by 2.5% from the ab-initio values; recent studies on rigid molecules with two to three heavy atoms showed that this parameter, when calculated at a high level of theory, is usually accurate to about 3% or better (Lattanzi et al 2011;Spezzano et al 2012). In Table 1 the HSCO + spectroscopic parameters are also compared with those derived by Brünken et al (2009) for HSCN.…”
Section: Discussionsupporting
confidence: 88%
“…This level of agreement is similar to that obtained with the same level of theory (CcCR QFF) recently reported for HOCO + (Bizzocchi et al 2017). For example, the experimental D J fourth-order distortion constant differs by 2.5% from the ab-initio values; recent studies on rigid molecules with two to three heavy atoms showed that this parameter, when calculated at a high level of theory, is usually accurate to about 3% or better (Lattanzi et al 2011;Spezzano et al 2012). In Table 1 the HSCO + spectroscopic parameters are also compared with those derived by Brünken et al (2009) for HSCN.…”
Section: Discussionsupporting
confidence: 88%
“…These include H 2 O + , SH + , SO + , HCS + , CO + , HOCO + , and NNH + . In addition to these, the HOSO + ion recently measured in the laboratory may also be a plausible species in VY CMa (Lattanzi et al 2011). We were unable to identify any of the positive molecular ions referred to -26here in our survey, nevertheless this band appears well suited for future searches for new molecular ions in this source.…”
Section: Molecular Ions and Recombination Linesmentioning
confidence: 69%
“…[1a] It appearst hat, despite the presence of thesen eutral and ionic species in severala strophysicale nvironments, there is an unexpected lack of both experimental and computational studies of their reactivity.I ni ts neutral (SO 2 )a nd cationic state (SO 2 · + )t he simplest, most fundamental and widespread reactions with ag eneral compound RÀHi nvolvep roton transfer (PT) from RÀH 0/ + to SO 2 and hydrogen atom transfer (HAT) from RÀHt oS O 2 · + ,b oth leading to the same ionic product, HSO 2 + . [8] Although the protonated sulfur dioxide has not yet been detected in space,t he growing field of interstellar ion chemistrya nd the rotationals pectra data collected in the laboratory [9] will probably help identifying this ion. Hence, reactions that produce HSO 2 + and the kinetic trend of the reaction with the temperature are relevant to understanding the reactiven etwork of sulfur-containing compounds.…”
Section: Introductionmentioning
confidence: 99%